1999
DOI: 10.1136/jms.6.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Two models for radiological reviewing of interval cancers

Abstract: Comparing the rate of missed cases from different studies may be misleading unless the same review method is used. No difference in detection rate could be shown whether the radiologist reviewed images from his/her own screening unit or not. Most of our interval cancers were not regarded as missed cases by either of the two methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…The results are also in agreement with the better possibilities to reduce mortality in older women compared with young women (9,10). The definition of an interval cancer varies (1,2,11,12) and is probably the main reason for the relatively high proportion of interval cancers in the last period of the interval compared with the incidence before the screening started. It is very difficult to achieve an exact interval for all the women in the target group, and this ''round slippage'' may be due to several factors, including administrative factors, changes to scheduled appointment etc.…”
Section: Screening and Interval Cancerssupporting
confidence: 82%
“…The results are also in agreement with the better possibilities to reduce mortality in older women compared with young women (9,10). The definition of an interval cancer varies (1,2,11,12) and is probably the main reason for the relatively high proportion of interval cancers in the last period of the interval compared with the incidence before the screening started. It is very difficult to achieve an exact interval for all the women in the target group, and this ''round slippage'' may be due to several factors, including administrative factors, changes to scheduled appointment etc.…”
Section: Screening and Interval Cancerssupporting
confidence: 82%
“…14 -17 However, immediate comparison of frequencies must be done with caution because of differences in inclusion criteria and screening protocol. 18,19 Early assessment after an unclear screening result is discouraged in the Norwegian Breast Cancer Screening Program's quality manual. Women who [15][16][17] However, when the interval was split in 2 periods, comparison of observed/expected ratios revealed that whereas our rate in the first year was in accordance with the reported proportionate incidences, our estimate of the second year (0.75) was higher than the corresponding figures from other programs (0.59 in East Anglia, 14 0.52 in Holland, 15 0.52 in North West England 16 and 0.54 in Victoria, Australia 17 ).…”
Section: Frequency Of Invasive Interval Cancersmentioning
confidence: 99%
“…The European guidelines (Perry et al, 2006) recommend screening units to monitor IC for purposes of internal audit and training. In screening programmes performing double reading with trained radiologists, only a small proportion of the IC are classified as interpretation errors (missed) (Moberg et al, 1999;Hofvind et al, 2006). In other instances they represent a limit of the test (occult or showing nonspecific mammographic signs) or arise in the screening interval; the longer the interval, the greater the risk of IC (Woodman et al, 1995;Klemi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%